Effectiveness Analysis of the CSR Program Gerakan Literasi Syariah (GEULIS) at PT. Bank Muamalat Indonesia Tbk, Using Present Value, Future Value, and Intrinsic Value Approaches - Dwi Cahyono, Andy; Dwi Haryanti, Agustin (Asian Journal of Social and Humanities, 2025)
This study aims to evaluate and assess the effectiveness of the Gerakan Literasi Syariah (GEULIS) Program made by PT. Bank Muamalat Indonesia Tbk. GEULIS Program is a financial education program for the younger generation that aims to increase Islamic financial literacy and inclusion in Indonesia. This research method uses a combination approach, namely qualitative and quantitative descriptive which aims to explore the impact of the program and measure it to determine the social value produced using the Social Return on Investment (SROI) model. This study shows that the GEULIS Program has produced significant social value with three approaches used, namely the present value approach produces a ratio of 1:4.06, future value with a figure of 1:4.87, and intrinsic value shows a figure of 1:4.43. The three ratios based on sensitivity analysis, show the consistency of the > 1 number, this means that the program has run effectively and has a significant impact. In addition, the impact generated by this program has contributed to SDGs 1, 3, 4, 8 and 9. Thus, the GEULIS Program must still strive to increase its effectiveness by implementing it more intensively and expanding the scope of the program.